2012
DOI: 10.1002/path.4019
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor treatment of breast cancer cells increases the expression of let‐7f, a microRNA targeting CYP19A1

Abstract: Aromatase inhibitors (AIs) are considered the gold standard of endocrine therapy for oestrogen receptor-positive postmenopausal breast cancer patients. AI treatment was reported to result in marked alterations of genetic profiles in cancer tissues but its detailed molecular mechanisms have not been elucidated. Therefore, we profiled miRNA expression before and after treatment with letrozole in MCF-7 co-cultured with primary breast cancer stromal cells. Letrozole significantly altered the expression profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 29 publications
9
46
0
Order By: Relevance
“…Treatment with the let-7f mimic resulted in an approximately 100-fold increase in let-7f expression compared with has-mir-negative control treatment (data not shown). Since let-7f has been shown to target the aromatase gene (4), we evaluated aromatase expression in Ishikawa cell lines and endometrial stromal cells from the patients with endometriosis after let-7f mimic transfection. After 48 hours of let-7f mimic treatment, aromatase mRNA expression was significantly decreased in both Ishikawa cell lines and endometrial stromal cells (0.36-fold increase, P =0.002 and 0.61-fold increase, P =0.025, respectively) (Figure 2A, B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with the let-7f mimic resulted in an approximately 100-fold increase in let-7f expression compared with has-mir-negative control treatment (data not shown). Since let-7f has been shown to target the aromatase gene (4), we evaluated aromatase expression in Ishikawa cell lines and endometrial stromal cells from the patients with endometriosis after let-7f mimic transfection. After 48 hours of let-7f mimic treatment, aromatase mRNA expression was significantly decreased in both Ishikawa cell lines and endometrial stromal cells (0.36-fold increase, P =0.002 and 0.61-fold increase, P =0.025, respectively) (Figure 2A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that AI treatment of breast cancer cells increases the expression of let-7f , a microRNA targeting aromatase gene (CYP19A1)(4). MicroRNAs (miRNAs) are a family of endogenous, small (approximately 22 nucleotides in length), noncoding, functional RNAs which regulate gene expression either by translational repression or degradation of messenger RNA transcripts after targeting the 3′ UTR.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs expression profiling before and after letrozole treatment reveal post-treatment increases in let-7f expression in both the preclinical and clinical settings. 62 miRNA and heat shock proteins in hormone receptor-positive/ HER2-negative breast cancer Heat shock protein (HSP) reveals various effects on multiple oncogenic signaling pathways. The function of HSP is generally considered to be ATP-dependent protein chaperoning.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…All enzymes are discussed in the text with the exception of oestrogen sulphotransferase (EST), which is an oestrogen-specific enzyme and hence outside the scope of this article, however, given its importance both biologically and therapeutically (reviewed by McNamara et al (2013b)) and as such is included in this diagram. Printed in Great Britain aromatase in ERa-positive MCF7 breast cancer cells (Shibahara et al 2012). Therefore, the protective actions of androgens, at least in ERa-positive breast cancers, may be partially achieved through down-regulation of aromatase and decreased intracrine synthesis of oestrogens.…”
Section: Intracrine Androgen Metabolism In the Breastmentioning
confidence: 99%